Population impact of direct-acting antiviral treatment on new presentations of hepatitis C-related decompensated cirrhosis: a national record-linkage study. Issue 12 (26th March 2020) - Hutchinson, Sharon J; Valerio, Heather; McDonald, Scott A; Yeung, Alan; Pollock, Kevin; Smith, Shanley; Barclay, Stephen; Dillon, John F; Fox, Raymond; Bramley, Peter; Fraser, Andrew; Kennedy, Nicholas; et al.
Abstract : Objective: Population-based studies demonstrating the clinical impact of interferon-free direct-acting antiviral (DAA) therapies are lacking. We examined the impact of the introduction of DAAs on HCV-related decompensated cirrhosis (DC) through analysis of population-based data from Scotland. Design: Through analysis of national surveillance data (involving linkage of HCV diagnosis and clinical databases to hospital and deaths registers), we determined i) the scale-up in the number of patients treated and achieving a sustained viral response (SVR), and ii) the change in the trend of new presentations with HCV-related DC, with the introduction of DAAs. Results: Approximately 11 000 patients had been treated in Scotland over the 8-year period 2010/11 to 2017/18. The scale-up in the number of patients achieving SVR between the pre-DAA and DAA eras was 2.3-fold overall and 5.9-fold among those with compensated cirrhosis (the group at immediate risk of developing DC). In the pre-DAA era, the annual number of HCV-related DC presentations increased 4.6-fold between 2000 (30) and 2014 (142). In the DAA era, presentations decreased by 51% to 69 in 2018 (and by 67% among those with chronic infection at presentation), representing a significant change in trend (rate ratio 0.88, 95% CI 0.85 to 0.90). With the introduction of DAAs, an estimated 330 DC cases had been averted during 2015–18. Conclusions: National scale-up in interferon-free DAA treatment is associated with the rapid downturn in presentations of HCV-related DC at the population-level. Major progress in averting HCV-related DC in the short-term is feasible, and thus other countries should strive to achieve the same.